Karakteristik Selai Kacang Mete dengan Perbandingan Kacang Mete (Anacardium occidentale L.) dan Gula Singkong (Manihot utilisima) - Lakhsmi Dewi, Ni Made Gayatri; Hapsari Arihantana, Ni Made Indri; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i02.p07, 2025)
Cashew nut jam is made from roasted cashew nuts added with sugar and salt and then mashed. The use of granulated sugar will cause the texture of jam to be less smooth and forming crystals on the surface of jam, so it requires other alternatives, such as cassava sugar. Using cassava sugar requires an appropriate concentration to obtain the best jam characteristics. This study aims to determine the effect of cashew nuts and cassava sugar ratio on the characteristics of jam and the proper ratio to produce jam with the best characteristics. This study used a completely randomized design (CRD) with a factor of cashew nut and cassava sugar ratio of 5 levels, namely 90:10, 80:20, 70:30, 60:40, and 50:50. Each treatment was repeated three times, resulting in 15 experimental units. The data was analyzed using ANOVA and followed by DMRT. The results showed that the ratio of cashew nuts and cassava sugar had a significant effect on the moisture content, ash content, protein content, fat content, total sugar content, hedonic test (color, aroma, texture, taste, and overall acceptance), and texture intensity. The ratio of 90 percent cashew nuts and 10 percent cassava sugar produced peanut butter with the best characteristics, namely moisture content of 2.54 percent, ash content of 2.28 percent, protein content of 19.65 percent, fat content of 41.02 percent, total sugar content of 3.05 percent, relatively easy to spread, slightly light brown color, aroma, smooth texture, taste, and overall acceptance are liked. Keywords: casava sugar, cashew nuts, peanut butter